Characteristics of COVID-19 in cancer patients: A cross-sectional study in Peru - Payet, Eduardo (2021)
Background: Cancer patients are at higher risk of infection and severity of Coronavirus Disease-19 (COVID-19). Management of patients infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is challenging due to the scarce scientific information and treatment guidelines. In this work, we present our Institutional experience with our first 100 patients with oncological malignancies and COVID-19. Patients and methods: We conducted a cross-sectional study of the first 100 patients hospitalised at the Instituto Nacional de Enfermedades Neoplasicas (Lima, Peru) who were positive for SARS-CoV-2 by reverse transcriptase (RT)-PCR during the period 30 March to 20 June. Clinicopathological variables of the oncological disease as well as risk factors, management and outcomes to COVID-19 were evaluated. Results: The mean age was 43.5 years old (standard deviations: ±24.8) where 57% were male patients. In total, 44%, 37% and 19% were adult patients bearing solid tumours, adults with haematologic malignancies and paediatric patients, respectively. Hypertension was the most frequent comorbidity (23%) followed by chronic lung disease (10%). COVID-19-associated symptoms included cough (65%), fever (57%) and dyspnoea (56%). Twelve percent of patients were asymptomatic. Nosocomial infections were more frequent in paediatric patients (84.2%) than in adult patients (16.0%). Patients with uncontrolled oncological disease were most frequent (72%). Anaemia was present in 67% of patients, 68% had lymphopenia, 62% had ferritin value > 500 mcg/L, 85% had elevated lactate dehydrogenase (LDH), 83% D-dimer > 500 ng/mL and 80% C-Reactive Protein > 8 mg/L. The most common complication was acute respiratory failure (42%). Overall fatality rate was 39% where the main cause of mortality was acute respiratory distress syndrome (64.1%). Conclusion: Paediatric patients had better outcomes than adult populations, and a high number of asymptomatic carriers and nosocomial infection, early diagnosis are recommended. Considering oncological treatments 30 days before COVID-19 diagnosis, our data did not reveal an increased mortality.